PERENCANAAN PEMBANGUNAN WISATA LINGKUNGAN DAN PENDIDIKAN DI KAWASAN PERKEBUNAN, KEHUTANAN PERIKANAN DAN PETERNAKAN DI DESA SWARANGAN KECAMATAN JORONG TANAH LAUT - Andi Ulfa Sufiadi; Udiansyah Udiansyah; Mufidah Asy'ari (Universitas Lambung Mangkurat, 2020)
Tourism development planning is an important part of a tourism area management. Tourism development planning in this study requires facilities and infrastructure that will support a tourism activity that will be made and find out the community's opinion regarding this tourism development planning. Development plans obtained by observing existing potential with the results obtained are potential in the form of forestry crops, agricultural crops, plantation crops, chicken, duck and goat farms and fish fishing ponds. Tourism development plans that will be planned in the form of halls, gajebo and outboard chairs, playgrounds, public toilets, trash bins, security posts, cattle, horses and rabbits, photo spots, tourist trains, decorative facilities, fences, signposts and artificial passageways. Selected respondents' opinions stated that they agreed and were interested in the development plan for education and environmental tourism because it provided opportunities for the surrounding community and increased tourist destinations in South Kalimantan.Keywords: Planning, development, potential, opinion